LKY on governance, management, life a collection of quotes from Lee Kuan Yew /ccurated by Janice Tay & Ronald Kow - Lee, Kuan Yew 1923-2015 (Straits Times Press Pte Ltd, Singapore Press Holdings, 2015)
LKY on governance, management, life : a collection of quotes from Lee Kuan Yew is the most accessible compendium ever published on the man widely regarded as Singapore's founding father